2013
DOI: 10.1007/s00330-012-2763-0
|View full text |Cite
|
Sign up to set email alerts
|

Methodological quality of diagnostic accuracy studies on non-invasive coronary CT angiography: influence of QUADAS (Quality Assessment of Diagnostic Accuracy Studies included in systematic reviews) items on sensitivity and specificity

Abstract: • Good methodological quality is a basic requirement in diagnostic accuracy studies. • Most coronary CT angiography studies have only been of moderate design quality. • Weak methodological quality will affect the sensitivity and specificity. • No improvement in methodological quality was observed over time. • Authors should consider the QUADAS checklist when undertaking accuracy studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 151 publications
1
4
0
Order By: Relevance
“…Schueler et al reported that item referring to how authors handled “Uninterpretable Results” (QUADAS item 13) had a significant influence on diagnostic accuracy values and that exclusion of uninterpretable results may overestimate the diagnostic abilities of the method being investigated[34], which has also been proven by our analysis. Salavati et al, on the other hand, did not detect a difference between studies including and excluding uninterpretable segments[35].…”
Section: Discussionsupporting
confidence: 75%
“…Schueler et al reported that item referring to how authors handled “Uninterpretable Results” (QUADAS item 13) had a significant influence on diagnostic accuracy values and that exclusion of uninterpretable results may overestimate the diagnostic abilities of the method being investigated[34], which has also been proven by our analysis. Salavati et al, on the other hand, did not detect a difference between studies including and excluding uninterpretable segments[35].…”
Section: Discussionsupporting
confidence: 75%
“…Studies of diagnostic accuracy compare the results of one or more tests under investigation with the results of the reference standard, which is the best available method for the detection of the target condition [1,2]. Such studies tend to be prone to bias and variation, especially concerning demographic features, disease prevalence and severity, clinical review bias, and observer and instrument variation [3][4][5][6][7][8]. Biased results have an impact on the recommendations of the test under consideration and can hamper their generalizability [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…We usedthe Quality Assessment of Diagnostic Accuracy Studies 2 (QUADAS-2) tool ( 16 ) to assesse the quality of the included studies independently by the two authors. The assessement of QUADAS-2 was based on four items: (1) how the cases were selected; (2) index test, it was the descriptions of how the studies were implented and how the results were interpretatd; (3) reference standard, it includes descriptions standards of the the references; (4) flow and timing, it includeshow the cases were included and excluded.…”
Section: Methodsmentioning
confidence: 99%